Phase engineering of transition metal dichalcogenides. (7th May 2015) - Voiry, Damien; Mohite, Aditya; Chhowalla, Manish
<x xml:space="preserve">Abstract</x> The co-existence of 2H, 1T and 1T′ phases in monolayered TMDs.